PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP KEMAMPUAN KAWIN MENCIT JANTAN (Mus musculus L. Swiss Webster) - Lumban Toruan, Juni Asmi; Sumarmin, Ramadhan; Indriati, Gustina (Pendidikan Biologi, 2014)
ABSTRACT Mangosteen ( Garcinia mangostana L. ) is one of tradisional medicine contains mangostin soul. Mangostin has effect to prevent cell division ( cytokinesis ). This research to determine the effect of extracts of mangosteen ( Garcinia mangostana L. ) on the mating ability of male mice ( Mus musculus L. Swiss Webster). This research use the male mice ( Mus musculus L.) by 4 treatment and 6 repetition. Treatment that is given is an extract of mangosteen with various dose are: treatment 1 is an control, treatment II, III, and IV are the treatments which are given the extract of mangosteen orally during 36 days with a dose of   0.2, 04 and 0.6 g / head / day. After the administration of mangosteen extract , mating ability test on each test 1 male mated with 5 female mice to see the amount of   intromision, the number of female mice pregnant female mice. The analyzed using ANOVA ( Analysis of Variance ) and then continue test with LSD test at α level of5%. The result showed an average movement of the control is 14,66 intromisi not significanty different from treatment A is 13,83 and decine intromisi movement occurs on treatment B with an average of 6,5 and an average of 5,66 C treatment. For the number of female mice in mamage to male mice in each treatment was not significanty different compared with controls mared each 2 tail. While the number of oregnant  female mice were successful, namely 2,33 in control and not significanty different  from treatment  A  with  an  average  of  2,00,  a  decrease in  the  average treatment B and C average 1,33 and 1,00 It can be concluded that the extract of mangosteen (Garcinia mangostana L.) were administered orally for 36 days at a does of o 0,4 g /head /day did not affect mating mice but decrease the number of pregnant female mice.